Trauma and Hemorrhagic Shock Activate Molecular Association of ALOX5 and ALOX5AP in Lung Tissue - Nunns, Geoffrey R. (J Surg Res, 2018)
BACKGROUND: Post-traumatic lung injury following trauma and hemorrhagic shock (T/HS) is associated with significant morbidity. Leukotriene-induced inflammation has been implicated in the development of post-traumatic lung injury through a mechanism that is only partially understood. Post-shock mesenteric lymph returning to the systemic circulation is rich in arachidonic acid (AA), the substrate of 5-lipoxygenase (ALOX5). ALOX5 is the rate-limiting enzyme in leukotriene synthesis and, following T/HS, contributes to the development of lung dysfunction. ALOX5 co-localizes with its cofactor, 5-lipoxygenase-activating protein (ALOX5AP), which is thought to potentiate ALOX5 synthetic activity. We hypothesized that T/HS results in the molecular association and nuclear co-localization of ALOX5 and ALOX5AP, which ultimately increases leukotriene production and potentiates lung injury. MATERIALS AND METHODS: To examine these molecular interactions, a rat T/HS model was employed. Post-T/HS tissue was evaluated for lung injury through both histologic analysis of lung sections and biochemical analysis of bronchoalveolar lavage fluid. Lung tissue was immunostained for ALOX5 and ALOX5AP with association and co-localization evaluated by fluorescence resonance energy transfer (FRET). Additionally, rats undergoing T/HS were treated with MK-886, a known ALOX5AP inhibitor. RESULTS: ALOX5 levels increase and ALOX5/ALOX5AP association occurred after T/HS, as evidenced by increases in total tissue fluorescence and FRET signal intensity, respectively. These findings coincided with increased leukotriene production and with the histological changes characteristic of lung injury. ALOX5/ALOX5AP complex formation, leukotriene production and lung injury were decreased after inhibition of ALOX5AP with MK-886. CONCLUSIONS: These results suggest that the association of ALOX5/ALOX5AP contributes to leukotriene-induced inflammation and predisposes the T/HS animal to lung injury.